COX-2 Inhibitors, Aspirin, and Other Potential Anti-Inflammatory Treatments for Psychiatric Disorders - Müller, Norbert (Frontiers in Psychiatry, 2019)
Inflammatory processes associated with persistent (chronic) infection have long been discussed as etiological factors in psychiatric disorders. Studies have found that people with major depression have higher levels of pro-inflammatory cytokines, e.g. IL-1, IL-6, and TNF-, and C-reactive protein. In schizophrenia, many reports have described raised levels of cytokines, e.g. IL-6, and meta-analyses have confirmed these findings. Microglia cells are important in inflammatory processes, and positron emission tomography studies have shown microglia activation in both depression and schizophrenia. As a consequence of the above findings, immunomodulation is widely discussed as a potential treatment approach in both major depression and schizophrenia. The COX-2 inhibitor celecoxib was found to have a significant positive effect in major depression, not only in single studies but also in meta-analyses. Celecoxib has also been studied in schizophrenia and shown efficacy, in particular in early disease stages. The mixed COX inhibitor aspirin (acetylsalicylic acid) seems to have both protective and therapeutic effects in schizophrenia. This paper discusses the hypothesized role of inflammation in major depression and schizophrenia, including markers of inflammation; pertinent studies on celecoxib and aspirin; and additional immunomodulatory therapeutic strategies.